Marker for Real-Time Analysis of Caspase Activity in Intact Cells. (December 2002) - Lee, Pui; Beem, Elaine; Segal, Mark S.
Apoptosis, or programmed cell death, is an important regulator of growth, development, defense, and homeostasis in multicellular organisms. A family of cysteine proteases known as caspases is central to many apoptotic pathways, and thus detection of their activity offers an effective means to assess apoptosis. However, currently available methods only allow the evaluation of in vivo caspase activity at a given time point or over a few hours. To assess the activity over extended periods of time, we designed a novel, real-time, in vivo marker that utilizes the Nend rule degradation pathway to allow the detection of caspase activity as reflected by increasing enhanced GFP (EGFP) stability. The marker has an N-terminal arginine in the absence of caspase activity and is rapidly degraded. In vivo caspase activity removes the marker's N-terminal arginine residue, leaving an EGFP with an N-terminal methionine that results in stable fluorescence. In our study, the marker accurately depicted an increase in caspase activity in apoptotic cells and also detected significant endogenous caspase activity in non-apoptotic cells. The downstream effects of this endogenous activity detected in intact, non-apoptotic cells must be regulated by the cell preventing apoptosis. These studies also demonstrate the feasibility of using the Nend rule to study endogenous enzymatic activities other than those associated with proteasomal degradation.